Podcast As An Affective Democratic Space: Political Framing and Youth Engagement in Mojok.Co's Putcast - Subkhi Ridho; Lala Affafa (Lektur: Jurnal Ilmu Komunikasi, 2025)
The rise of digital media has profoundly reshaped how Indonesian citizens engage in political discourse. This study explores how Mojok.co's Putcast functions as an affective democratic space and a medium of political education for young audiences. Employing a qualitative approach that combines content analysis, grounded theory, and in-depth interviews with the editorial team, this research analyzes two podcast episodes: "Inaya Wahid: Lengsernya Gus Dur Bikin Trauma Politik Sampai Sekarang" and "Dimas Oky Nugroho: Mereka Menghancurkan Mimpi Anak Muda Indonesia!" Findings reveal that Mojok.co strategically employs humor, satire, and reflective narratives to frame political issues surrounding Indonesia's Constitutional Court decision No. 90/PUU-XXI/2023 and the role of youth in democratic participation. The podcast's framing encourages audiences to negotiate political meanings emotionally and deliberatively. Analysis of YouTube comment sections demonstrates active audience participation in three forms: reflective (developing personal political opinions), affective-educative (expressing empathy and learning), and critical-negotiative (reinterpreting the podcast's frames). This study affirms theories of digital democracy and mediatization, suggesting that podcasts function not merely as information channels but as participatory arenas of political discourse. Mojok.co's Putcast exemplifies how local alternative media can democratize political conversations through affective engagement, egalitarian language, and technological accessibility. Hence, this study contributes to contemporary scholarship on digital political communication and proposes podcasting as a strategic medium for youth political literacy and affective democracy in Indonesia. Keywords: podcast Mojok.co, affective democracy, political framing, digital participation, political communication